Natural clay and biopolymer-based nanopesticides to control the environmental spread of a soluble herbicide - Granetto, Monica; Serpella, Luca; Fogliatto, Silvia; Re, Lucia; Bianco, Carlo; Vidotto, Francesco; Tosco, Tiziana (The Science of the total environment, 2022)
In this work a novel nano-formulation is proposed to control leaching and volatilization of a broadly used herbicide, dicamba. Dicamba is subject to significant leaching in soils, due to its marked solubility, and to significant volatilization and vapor drift, with consequent risks for operators and neighbouring crops. Natural, biocompatible, low-cost materials were employed to control its dispersion in the environment: among four tested candidate carriers, a nanosized natural clay (namely, K10 montmorillonite) was selected to adsorb the pesticide, and carboxymethyl cellulose (CMC), a food-grade biodegradable polymer, was employed as a coating agent. The synthesis approach is based on direct adsorption at ambient temperature and pressure, with a subsequent particle coating to increase suspension stability and control pesticide release. The nano-formulation showed a controlled release when diluted to field-relevant concentrations: in tap water, the uncoated K10 released approximately 45% of the total loaded dicamba, and the percentage reduced to less than 30% with coating. CMC also contributed to significantly reduce dicamba losses due to volatilization from treated soils (e.g., in medium sand, 9.3% of dicamba was lost in 24 h from the commercial product, 15.1% from the uncoated nanoformulation, and only 4.5% from the coated one). Moreover, the coated nanoformulation showed a dramatic decrease in mobility in porous media (when injected in a 11.6 cm sand-packed column, 99.3% of the commercial formulation was eluted, compared to 88.4% of the uncoated nanoformulation and only 24.5% of the coated one). Greenhouse tests indicated that the clay-based nanoformulation does not hinder the dicamba efficacy toward target weeds, even though differences were observed depending on the treated species. Despite the small (lab and greenhouse) scale of the tests, these preliminary results suggest a good efficacy of the proposed nanoformulation in controlling the environmental spreading of dicamba, without hindering efficacy toward target species. [Display omitted] •Natural clay and food-grade biopolymer are used in a novel nanopesticide formulation.•Natural clays showed effective in reduce environmental drawbacks of agrochemicals.•The nanoformulation effectively encapsulated dicamba and controlled its release.•The nanoformulation significantly reduced dicamba mobility in porous media.•The herbicidal efficacy of dicamba was not hindered by the nanoformulation.